Docetaxel-loaded liposomes: preparation, pH sensitivity, Pharmacokinetics, and tissue distribution - Hong Zhang; Rui-ying Li; Xia Lu; Zhen-zhen Mou; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2012)

Metal-Binding Activity of the Soluble Recombinant Pig Metallothionein 1A Expressed in Escherichia coli - Dongbo Sun; Hong Zhang; Guojun Wu; Qinghe Zhu; Siwen Lv; Donghua Guo; Rui Wu; Jun Bao (Biological Trace Element Research, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

A New bis(rhodamine)-Based Fluorescent Chemosensor for Fe3+ - Xiaopo Chen; Huijie Hong; Rui Han; Di Zhang; Yong Ye; Yu-fen Zhao (Journal of Fluorescence, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Chemical composition and antioxidant activities of extracts from Apocyni Veneti Folium - Sui-Hong Yan; Ying-Yong Zhao; Hai-Song Zeng; Yongmin Zhang; Rui-Chao Lin; Wen-Ji Sun (Natural Product Research, 2012)

Phylogenetic relationships between Leymus (Poaceae, Triticeae) and related diploid Triticeae species based on isozyme and genome-specific random amplified polymorphic DNA (RAPD) markers - Rui-Wu Yang; Min-Han Zhong; Xue-Mei Zou; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou (Plant Biosystems, 2012)

Metagenomic analysis of DNA viruses in a wastewater treatment plant in tropical climate - Hideyuki Tamaki; Rui Zhang; Florent E. Angly; Shota Nakamura; Pei‐Ying Hong; Teruo Yasunaga; Yoichi Kamagata; Wen‐Tso Liu (Environmental Microbiology, 2012)
Summary Viruses have been detected in the different stages of wastewater treatment plants (WWTPs) at concentrations of 10 8 –10 10 ml −1 of virus‐like particles (VLPs), 10–1000 times higher than in natural aquatic environments, suggesting that WWTPs can be considered as an important reservoir and source of viruses. This study revealed novel diversity and function with the DNA viral communities in the influent, activated sludge, anaerobic digester, and effluent of a domestic WWTP using metagenomics. WWTP was a very specific environment, with less than 5% of the > 936 000 metagenomic sequences obtained (∼70–119 Mbp per sample) similar to sequences present in other environmental viromes. Many viruses found in the WWTP were novel, resulting in only 82% were shared. These data suggested that VLPs of most viral types could be present between 1 and 30 days in the process before they were discharged. Viruses in WWTP and the discharged ones can have potential impacts on the functioning of the wastewater treatment system and on the dynamics of microbial community in the surrounding aquatic environments respectively.